2009
DOI: 10.1021/bi9017895
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Fusion Peptides of Tick-Borne Encephalitis Virus as Models for Membrane Fusion

Abstract: The fusion peptide of TBEV is a short segment of the envelope protein that mediates viral and host cell membrane fusion at acidic pH. Previous studies on the E protein have shown that mutations at L107 have an effect on fusogenic activity. Structural studies have also suggested that during the fusion process the E protein rearranges to form a trimer. In the present study, a number of short peptides were synthesized, and their structure/activity was examined: (1) monomers consisting of residues 93-113 of the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 74 publications
1
57
1
2
Order By: Relevance
“…It has recently been proposed that the flavivirus histidines function as molecular switches, and they therefore control the fusion process by acting as pH sensors in the Flavivirus membrane fusion process [27]. However, a recent work publication showed that His104 protonation does not inhibit the ability of TBEV FP to bind to membranes [28]. Indeed, the data presented here, as well as in other studies, suggest that this is not the case for His104 in TBEV FP.…”
Section: Discussioncontrasting
confidence: 51%
“…It has recently been proposed that the flavivirus histidines function as molecular switches, and they therefore control the fusion process by acting as pH sensors in the Flavivirus membrane fusion process [27]. However, a recent work publication showed that His104 protonation does not inhibit the ability of TBEV FP to bind to membranes [28]. Indeed, the data presented here, as well as in other studies, suggest that this is not the case for His104 in TBEV FP.…”
Section: Discussioncontrasting
confidence: 51%
“…Fusion of some enveloped viruses other than HIV (such as influenza) occurs in the acidified endosome at pH between 5 and 6 (Pan et al 2010; White et al 2008). This has motivated earlier studies that examined the pH dependence of vesicle fusion induced by influenza fusion protein constructs including the full ectodomain with fusion peptide (Curtis-Fisk et al 2007; Epand et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in the absence of the linker, the core trimer is unstable. Studies of a synthetic flavivirus fusion peptide suggested that residues in the fusion loop can affect trimer stability (35). Although G91D E1 inserts into target membranes and forms the extended trimer, intratrimer interactions of the fusion loops may be disrupted.…”
Section: Discussionmentioning
confidence: 99%